Is Folk Dance Still Thriving? Personal Experience and Interest in Philippine Traditional Dances as a Basis on Strengthening the Love for Culture and the Arts - Joseph T. Lobo (Ilmu Inovasi Nusantara, 2022)
A correlational study which aims to determine the relationship between the level of personal experience and level of interest of students taking BPEd and BPeA at City College of Angeles towards Philippine traditional Dances. Frequency and percentage were used to determine the number of students who answered the online survey questionnaire, while Pearson r was used to determine the relationship between personal experience and interest. The study findings shown that most of the respondents has an average experience in Philippine traditional dances. It was also found out that most of the respondents are interested in learning folk dance in respect to dance steps, music, costume and dance history. Lastly, it was found out that the level of personal experience and level of interest of students to Philippine traditional dances are significantly related to each other. Based on the findings of the study, proposed dance programs/activities will be provided which can be part of the projects of the institute, to intensify their appreciation to the culture and arts of the Philippines steered by one of the core values of the college – Patrimony. Limitation of this study is, it only focuses on BPEd and BPeA students. Additional respondents from other programs which are not part of this study is highly recommended